2018
DOI: 10.1016/j.cjca.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Remote Automated Monitoring: Need for and State of the Science

Abstract: Worldwide, more than 230 million adults have major noncardiac surgery each year. Although surgery can improve quality and duration of life, it can also precipitate major complications. Moreover, a substantial proportion of deaths occur after discharge. Current systems for monitoring patients postoperatively, on surgical wards and after transition to home, are inadequate. On the surgical ward, vital signs evaluation usually occurs only every 4-8 hours. Reduced in-hospital ward monitoring, followed by no vital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 54 publications
0
103
0
Order By: Relevance
“…The potential benefits of continuous remote wireless patient monitoring are increasingly recognized. 16,[42][43][44] A recent review by Downey et al 45 concluded that continuous monitoring outside critical care settings is feasible and may show patient benefits in terms of improved outcomes and cost efficiency. Another review suggested that implementation of remote monitoring with automated notifications increased involvement of ward physicians, rather than increased rapid response teams activation.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…The potential benefits of continuous remote wireless patient monitoring are increasingly recognized. 16,[42][43][44] A recent review by Downey et al 45 concluded that continuous monitoring outside critical care settings is feasible and may show patient benefits in terms of improved outcomes and cost efficiency. Another review suggested that implementation of remote monitoring with automated notifications increased involvement of ward physicians, rather than increased rapid response teams activation.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…However, the number and quality of studies was too low to allow final conclusions. Recent publications support the need for continuous ward monitoring [48,49], and several different systems are available, including new measurement techniques [50,51]. In the current study we demonstrated that with the used wireless monitoring system it is feasible to electronically measure RespR up to 4 days post-operatively on the ward.…”
Section: Discussionmentioning
confidence: 57%
“…To our knowledge, the use of remote monitors for MAP, HR and SpO 2 has never been evaluated in ambulatory surgery. Similar systems have been extensively tested and evaluated in cardiology, oncology and diabetes [ 17 20 ]. In these cases, they have contributed to optimising remote medical monitoring and adapting treatments [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar systems have been extensively tested and evaluated in cardiology, oncology and diabetes [ 17 20 ]. In these cases, they have contributed to optimising remote medical monitoring and adapting treatments [ 20 ]. In this sense, after ambulatory surgery, these monitors may be effective in detecting early postoperative adverse events in patients at home.…”
Section: Discussionmentioning
confidence: 99%